Hypothalamic estrogen receptor alpha establishes a sexually dimorphic regulatory node of energy expenditure - van Veen, J. Edward (Nat Metab, 2020)
Estrogen receptor a (ERa) signaling in the ventromedial hypothalamus (VMH) contributes to energy homeostasis by modulating physical activity and thermogenesis. However, the precise neuronal populations involved remain undefined. Here, we describe six neuronal populations in the mouse VMH by using single-cell RNA transcriptomics and in situ hybridization. ERa is enriched in populations showing sex biased expression of reprimo (Rprm), tachykinin 1 (Tac1), and prodynorphin (Pdyn). Female biased expression of Tac1 and Rprm is patterned by ERa-dependent repression during male development, whereas male biased expression of Pdyn is maintained by circulating testicular hormone in adulthood. Chemogenetic activation of ERa positive VMH neurons stimulates heat generation and movement in both sexes. However, silencing Rprm gene function increases core temperature selectively in females and ectopic Rprm expression in males is associated with reduced core temperature. Together these findings reveal a role for Rprm in temperature regulation and ERa in the masculinization of neuron populations that underlie energy expenditure.